2007
DOI: 10.1111/j.1349-7006.2007.00488.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between liver metastasis of the colocalization of actin‐related protein 2 and 3 complex and WAVE2 in colorectal carcinoma

Abstract: Directed movement of normal cells occurs when actin-related protein 2 and 3 complex (Arp2/3 complex) triggers the actin polymerization that forms lamellipodia immediately after binding to WAVE2. In order to determine whether the same mechanism correlates with liver metastasis from colorectal cancer, paired mirror sections of 154 cancer specimens (29 cases with liver metastasis and 125 cases without liver metastasis in which T factor, gender, primary tumor site, and age at operation were matched) were examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 40 publications
5
60
0
1
Order By: Relevance
“…Of some note are the CDCP1/ PKCy transmembrane signaling complex involved in survival (25), the E-cadherin/catenins complexes in mesenchyme induction and cell motility (2), and proteins of the ERM family in cell invasion (26). Additionally, Src targets the Wave2 and the a6/h4 integrin complexes, recently identified as novel players of epithelial cell motility/invasion (27,28). We also noticed a subgroup of signaling proteins that regulate the small GTPases of the Rho family, and which may modulate actinic cytoskeleton occurring during cell invasion (26).…”
Section: Resultsmentioning
confidence: 99%
“…Of some note are the CDCP1/ PKCy transmembrane signaling complex involved in survival (25), the E-cadherin/catenins complexes in mesenchyme induction and cell motility (2), and proteins of the ERM family in cell invasion (26). Additionally, Src targets the Wave2 and the a6/h4 integrin complexes, recently identified as novel players of epithelial cell motility/invasion (27,28). We also noticed a subgroup of signaling proteins that regulate the small GTPases of the Rho family, and which may modulate actinic cytoskeleton occurring during cell invasion (26).…”
Section: Resultsmentioning
confidence: 99%
“…The activity of the Arp2/3 complex itself is controlled by actin nucleation-promoting factors, such as the N-WASP or the Scar/WAVE complexes which are themselves recruited to and activated at the membrane by Rac1 [172][173][174]. Increased expression of Arp2/3 and WAVE2 has been shown to correlate with poor prognosis in breast and liver carcinomas underlining the relevance of lamellipodia-like structures in cancer progression [175,176]. Furthermore, the formation of lamellipodia is also observed upon ErbB2-driven EMT in epithelial cells, indicating that the formation of lamellipodia-like structures underlies the increased invasiveness observed during EMT [177].…”
Section: Lamellipodia and Filopodiamentioning
confidence: 99%
“…WAVE2 expression is elevated in human hepatocellular carcinoma, which correlates with a poor prognosis (11). In addition, colocalization of WAVE2 and the Arp2 is an independent risk factor for liver metastasis originating from colorectal carcinoma (12), and enhancement of WAVE2 expression facilitates the invasion of breast cancer cell line MDA-MB-231 (13). Recently, Yao et al (14) found that WAVE2 was over expressed in gastric cancer cells and there was a significant correlation between WAVE2 protein levels and the migration/invasion of gastric cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%